The image of Spain for an impertinent curious in the twentieth century: "Vaya país", John Hooper and William Chislett - Cano Jiménez, Gema (Historia y Comunicación Social, 2017)
The article that we present shows an analytical research through three works that foreign journalists dedicated to Spain in three moments of our current history. Thus we begin with the study Vaya país, the vision on different aspects of the Spanish life of ten foreign correspondents. We continue with the analysis of William Chislett; An indispensable reference in the vision of the Transition. And, finally, the study of The New Spaniards, a guide that exceeds the tourist aspects to offer a political and social analysis of Spain. We intend to show that along with well-grounded reflections, other stereotypes also survive, which is surprising due to the date of their publication.